THE RELATIONSHIP BETWEEN MOTHER'S PARENTING PATTERNS AND DIFFICULT EATING BEHAVIOR IN PRE-SCHOOL AGE CHILDREN - Mila, Alvika; Kurniawan, Vendi Eko; Zatihulwani, Eliza Zihni (Nurse and Holistic Care, 2023)
Background: Factor one mother complained that her child was very difficult to eat and only wanted to eat food when gathering with friends or invited to refresh. Objective: The purpose of the study was to determine the relationship between maternal parenting and difficult eating behavior in preschool age children in Pertiwi Kindergarten, Mancar Village, Peterongan District, Jombang Regency. Methods: The research design used correlational analysis with a cross sectional approach. The population of all mothers who have children in Pertiwi Kindergarten is 36 respondents with a total sampling technique so that a sample of 36 respondents is obtained. Collecting data using a questionnaire. The statistical test used in this study was Spearmen Rank Test. Result: The results showed that the permissive mother's parenting style with difficult eating behavior in children was mostly sufficient as many as 19 people (52.8). While the behavior of difficult eating in children with an authoritarian parenting pattern is as small as 3 people (8.3%). Spearmen Rank test showed value 0.000 (r value < 0.05). Then H1 is accepted, which means that there is a relationship between maternal parenting patterns and difficult eating behavior in preschool-aged children in Pertiwi Kindergarten, Mancar Village, Jombang Regency. Conclusion: Good parenting patterns for children who have difficulty eating so that nutritional factors do not occur are expected to provide interesting food so that children do not get bored with the food provided, limit the consumption of snacks and snacks that make children full before eating the main meal, and provide types of food that are suitable for children. nutrition for children. Trying to get children to eat by feeding and teaching children to eat new types of food.